Centering Orality in the Music History Classroom - Elizabeth Elmi (Musica Docta)
Music scholarship and pedagogy have historically privileged the written record for obvious reasons. Although music itself is an ephemeral art, our work as historians and teachers necessitates precise documentation, and to document something requires writing. Histories of medieval and early modern music, in particular, have tended to focus on the most precisely notated and beautifully adorned written evidence – precious objects made for and by the most economically and politically powerful communities of the day. But what do we lose when we focus on the richest forms of writing to the exclusion of all else? What about the thousands of others who sang and danced and played in various traditions and languages and cultures throughout the medieval and early modern world? How can we change our approach to both scholarship and teaching in a way that re-centers those marginalized voices? In this essay, I suggest the answer lies in a more dedicated study of oral musical traditions, not just as precursors to written ones but as self-sufficient and lasting practices of music-making in their own right. And, I argue, this study requires that we recognize explicitly, both in our scholarship and in our teaching, the fact that the story told to us by the extant written sources is incomplete and often biased. In addressing these issues, I will present a brief pedagogical example of how I center questions of orality in the early music history classroom through a mix of written documentation, including historical descriptions, iconographic evidence, and collections of musical works with and without notation.